Tuning Pressure Drop in Isoporous Membranes: Tuning Pressure Drop in Isoporous Membranes: Design with Fabrication Variability (Adv. Theory Simul. 8/2021). Issue 8 (6th August 2021) - Ong, Shi Ke; Birgersson, Erik; Low, Hong Yee
Abstract : In article number 2100088, Shi Ke Ong, Erik Birgersson, and Hong Yee Low develop a physics‐based machine learning methodology: the inherent fabrication variabilities (probability distributions) in the pore architecture of isoporous membranes and a trained neural network that aids in the performance range prediction through Monte Carlo simulations. Input and output are scaled [−1 1], hence the background has the digits '−1', '0' and '1'.